Roman amphora production in the Algarve (Southern Portugal) - Bernardes, João Pedro (2018)
During the Roman period, pottery production was disseminated across the Algarve region, mainly on the coast, and in most cases it has a direct connection with fish-salting units. Somewhat fewer than ten production sites are known to have manufactured amphorae and complementarily domestic pottery and building ceramics, although on only five of them have the fabrics been studied and published. The site at Martinhal on the westernmost part of the coast deserves to be specially highlighted, since it is the only one where the dimensions of the production area are better known, and there are features that allow the evaluation of the structures that supported the production. Most of these production centres began in the 3rd century AD and were dedicated mostly to the manufacture of amphorae to contain and transport fish products, such as types Almagro 50, Almagro 51c and Almagro 51a-b/Algarve 1. Local production prior to the 3rd century was rare, and the only workshops known were located in the eastern Algarve, in S. Bartolomeu de Castro Marim and in Manta Rota, where a late variant of type Dressel 14 was produced. The increase in fish salting from the 3rd century onward certainly contributed to the affirmation of the pottery production units in the region.